The moonstone / Retold by Tony Evans - Collins, Wilkie (Singapore Read Reads, 2011)
When Rachel Verinder inherits the Moonstone from her uncle on her eighteenth birthday, the wonderful jewel is intended to make her rich and happy. So why is her mother so worried about this valuable gift? Rachel seems very fond of her cousin, Franklin Blake. When trouble strikes, why does she refuse his help? What has he done to offend her? Can Sergeant Cuff, the famous detective, solve the dangerous mystery of the Moonstone before it is too late?
Q
b
b